Discurso político religioso brasileiro contemporâneo no YouTube: uma perspectiva multidimensional - Paes, Guilherme de Oliveira (2025)
This study investigates how religious and political discourses are linguistically articulated, analyzing the discursive mechanisms employed in this intersection. The study adopts a corpus-based approach, combining quantitative and qualitative methods to identify lexical and rhetorical patterns in language use. This study centers on the discourse of Silas Malafaia, one of the most prominent figures in Brazilian political-religious activism. The research objectives include analyzing his rhetorical strategies, identifying thematic patterns, and understanding the ideological structures underlying his discourse. Additionally, the study examines whether different dimensions of his discourse overlap, exploring the linguistic and contextual factors that enable these intersections. The corpus consists of 2,000 transcriptions of videos collected from his official YouTube channel, spanning a ten-year period (April 2014 – April 2024). These transcriptions were generated using YouTube's automatic speech recognition and were processed using computational scripts for lemmatization, part-of-speech tagging, and frequency analysis. The Lexical Multidimensional Analysis revealed three distinct discursive dimensions: (1) Moral and Spiritual Authority in Personal and Community Life, (2) Politically Motivated Religious Conservatism, and (3) Religious Moralism and Mobilization Against Gender Policies. These dimensions highlight how the discourse intertwines religion, politics, and morality, constructing a narrative that opposes progressive agendas and legitimizes conservative stances. The study also finds significant overlap between religious, political, and moral arguments, demonstrating how political issues are reframed within a religious framework to mobilize support. The research identifies key discursive strategies, including the use of polarizing rhetoric, constitutional appeals to justify ideological stances, and personification of political sectors. The results contribute to the understanding of political-religious discourse in Brazil, emphasizing the role of language in shaping public debate. The findings also suggest the need for further research into other political-religious figures to better understand the broader discursive landscape at the intersection of religion and politics in the country